The Sapphist images in the cinema in Turkey - Ulaşan, Atılgan Şahin (My University, 2019)
Cinema, which is one of the mass media, has been playing an important role in the representation of queers around the world for years. Considering the relationship between cinema and reality, it has been observed that the representations of queers in cinema have been negative and/or have created stereotypes about them. Among queers, Sapphists (women who love other women and/or find them sexually attractive) are one of the most negatively represented and stereotyped groups in the mainstream cinema and in the cinema in Turkey. In both cinemas, the tomboy, pansy and effeminate/butch stereotypes have been used to label queer appearance on the screen. These stereotypical representations in cinema are not only maintained on the character level but also on the narrative level. Since the early examples of cinema, representation of queers and Sapphists have been formed around the plots that relate these characters with crime, sex work, villainy, depravation and ludicrousness. In this study, the creation of the Sapphist stereotypes and in which narrative context Sapphist have been given in the cinema in Turkey will be questioned. To that aim, eleven films that include Sapphist characters will be analysed by using the sociological film interpretation method under the concepts of binarity, misandry and lesbian feminism, masculinity and violence, obscurity and villainy regarding their repetitive usage for the Sapphist representation.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Sapphist; Lesbian; Queer; LGBTQ; Image; Stereotype; Temsil; Müphemlik; Obscurity; Representation